Skin wound healing in obese and lean male adolescent rats submitted to pre-weaning litter size manipulation - Sabol, František; Bobrov, Nikita; Novotný, Martin; Vasilenko, Tomáš; Mozeš, Štefan; Šefčíková, Zuzana; Molčányiová, Angela; Tkáčová, Ružena; Tomori, Zoltán; Gál, Peter (Folia biologica (Praha), 2014)
We investigated whether early postnatal over-nutrition affects normal course of skin wound healing. To induce over-nutrition the litter size was adjusted on the first day after birth to four pups/nest (small litters). In parallel, as a control, normal nests of 10 pups/nest (normal litters) were used. For the wound healing experiment 30 male Sprague-Dawley rats, 15 from normal nests and 15 from small nests, were used. Two parallel full-thickness skin incisions and two full-thickness excisions were performed on the back of each rat. Samples for histological examination (excisions) and wound tensile strength measurement (incisions) were collected on days 2, 6, and 14 after surgery. Our study demonstrates that rats from the small nests had enhanced plasma levels of insulin and enhanced body weight/fat parameters. Furthermore, in small nests, rats that expressed the above-mentioned symptoms displayed slight improvement of epidermis regeneration, accelerated demarcation line formation, and increased wound tensile strength. From this point of view the small nest model used in the present experiment is helpful for exploration whether these acquired changes might be considered as a sufficient essential factor involved in the regulation of metabolic homeostasis and wound repair in juvenile obese male rats. Nevertheless, further studies need to be performed to verify the present findings also on other animal models and humans and to describe the exact underlying mechanism.
Keywords: modely nemocí na zvířatech; Animals; Rats, Sprague-Dawley; novorozená zvířata; krysa rodu Rattus; odstavení; obezita; mužské pohlaví; hojení ran; věda o výživě zvířat; pevnost v tahu; Rats; Weaning; Tensile Strength; Male; Insulin; Animal Nutrition Sciences; Disease Models, Animal; zvířata; homeostáza; Litter Size; Metabolic Syndrome; Obesity; Body Weight; inzulin; Skin; tělesná hmotnost; Wound Healing; velikost vrhu; Animals, Newborn; metabolický syndrom; potkani Sprague-Dawley; kůže; Homeostasis